Pastoral urbana: Un reto para la iglesia hoy - Zúñiga Rodríguez, Wilfrido (Revista Albertus Magnus, 2021)
The Urban ministry is a proposal for modern times that require reinterpretation of the different areas where there is life. Believers or atheists, are invited to understand the existence in terms of religious status, if we understand this principle (religious condition) as the ability to conceive that life is sacred that is a gift, inviting you to share it, as an existential imperative in the world. This preamble encourages us to propose this text as objective: to show without pontificating some requirements that you may require this new proposal from the mission of the church today which seeks to, praxis and the action, be understood as how to live and how to inhabit a world under the parameters of the image of a forgiving God (pastoral) in order to articulate: evangelizer and evangelized, message and messenger, theory and praxis, human life and experience of God, in the to give meaning search integrator message of the good news of Jesus of Nazareth in an age whose main feature is not only social fragmentation but also individually.